2017
DOI: 10.21037/jtd.2017.04.42
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients at higher risk of pneumonia after lung resection

Abstract: Background: Pneumonia is considered as one of the most common and serious complications after lung resection. The purpose of this study was to identify the risk factors associated with postoperative pneumonia (POP) after lung resection and to develop a scoring system to stratify patients with increased risk of POP.Methods: A retrospective review of a prospective database of patients between September 2014 and June 2016 was carried out. Logistic regression analysis was used to examine the risk factors for POP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…Clinical studies have identified several risk factors for postoperative pneumonia in lung cancer patients. Wellknown risk factors are as follows: old age (> 60 years), histopathological type of squamous cell carcinoma [4], smoking (current or previous), and the extent of excision of more than one lobe [5]. Risk factors for post bronchoscopy pneumonia in lung cancer patients are older age (> 70 years), current smoking, and central location of the tumor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have identified several risk factors for postoperative pneumonia in lung cancer patients. Wellknown risk factors are as follows: old age (> 60 years), histopathological type of squamous cell carcinoma [4], smoking (current or previous), and the extent of excision of more than one lobe [5]. Risk factors for post bronchoscopy pneumonia in lung cancer patients are older age (> 70 years), current smoking, and central location of the tumor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [14] have reported that old age is associated with the development of bacterial pneumonia in patients after cytotoxic chemotherapy in advanced lung cancer patients. Age ≥ 64 years was an independent predictors for post-operative pneumonia in lung cancer patients [5]. The elderly have several risk factors of pneumonia occurrences because of their impaired physical conditions.…”
Section: Discussionmentioning
confidence: 85%
“…Wang et al [4] have demonstrated that being old aged (> 60 years) and having squamous cell carcinoma histopathological type might be important risk factors of postoperative pneumonia in lung cancer patients after surgery. Liu et al [5] have reported that patients with older age, smoking, and extent of excision of more than one lobe have a higher risk for pneumonia after lung cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have identified several risk factors for postoperative pneumonia in lung cancer patients. Well-known risk factors are as follows: old age (> 60 years), histopathological type of squamous cell carcinoma [4], smoking (current or previous), and the extent of excision of more than one lobe [5]. Risk factors for post bronchoscopy pneumonia in lung cancer patients are older age (> 70 years), current smoking, and central location of the tumor [6].…”
Section: Introductionmentioning
confidence: 99%